Vitamin D Status Is Not Associated With Orthostatic Hypotension in Older Adults. - O'Halloran, Aisling; Molloy, Anne; Kenny, Rose; O'Connor, Deirdre (My University, 2019)
There has been much interest in investigating vitamin D status with orthostatic hypotension. However, studies have been small, inconsistent, and with a lack of standardization. The aim of this study was to investigate the association with vitamin D status in a large, nationally representative older adult population using a traceable standard of measurement and an accurate assessment of beat-to-beat blood pressure (BP). This study used participants aged >50 years from The Irish Longitudinal Study on Ageing. Impaired stabilization of BP on standing was defined as a sustained drop of ≥20 mm Hg systolic BP or ≥10 mm Hg diastolic BP up to 40 seconds post stand (impaired stabilization of BP on standing). We also analyzed participants who sustained a drop of ≥20 mm Hg systolic BP or ≥10 mm Hg diastolic BP throughout the 110 seconds stand (OH110). Vitamin D was categorized into sufficient (≥50 nmol/L), insufficient (30–50 nmol/L), and deficient (<30 nmol/L) status. After exclusion criteria 4209 participants were included. Those with deficiency were more likely to be smokers, take antihypertensive medications and had higher levels of cardiovascular disorders compared with those with sufficient status. In a univariate logistic regression those with deficient (odds ratio, 1.18; 95% CI, 0.86–1.61; P=0.303) or insufficient (odds ratio, 1.13; 95% CI, 0.91; P=0.272) status were no more likely to have evidence of impaired stabilization of BP on standing on active stand compared with sufficiency. Similar findings were found for OH110: deficient (odds ratio, 0.85; 95% CI, 0.52–1.40; P=0.528) or insufficient (odds ratio, 0.86; 95% CI, 0.61–1.21; P=0.384) versus sufficiency. In conclusion, vitamin D is not significantly associated with orthostatic hypotension in older adults. (Hypertension. 2019;74:639-644
PUBLISHED
Keywords: adult, aging, blood pressure, hypotension, vitamin D; Ageing; AGEING; CARDIOVASCULAR DISORDERS; VITAMIN D